FDI Spillovers, Financial Markets, and Economic Development - Sayek, Selin (IMF Working Papers; Working Paper ;, 2003)
This paper examines the role financial markets play in the relationship between foreign direct investment (FDI) and economic development. We model an economy with a continuum of agents indexed by their level of ability. Agents can either work for the foreign company or undertake entrepreneurial activities, which are subject to a fixed cost. Better financial markets allow agents to take advantage of knowledge spillovers from FDI, magnifying the output effects of FDI. Empirically, we show that well-developed financial markets allow significant gains from FDI, while FDI alone plays an ambiguous role in contributing to development.